TEACHER’S CODE SWITCHING IN ENGLISH CLASSROOM INSTRUCTION OF SEVENTH GRADE AT SMP NEGERI 13 MEDAN - Indah Syafitri; Ade Aini Nuran (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2023)
The objectives of this study are to find the types of code switching use by the teachers in providing English classroom instruction and to describe the reasons why the teachers use code switching in English classroom instruction at seventh grade of SMP Negeri 13 Medan. This study was conducted on English teachers of seventh grade at SMP Negeri 13 Medan. Descriptive qualitative research design was used as a research method while in data collection, observation, video recording, and interview were used in this study. The results showed that (1) in English classroom instruction of seventh grade that the teachers use three types of code switching namely 9 utterances in tag switching, 10 utterances with inter-sentential switching, and 43 utterances in intra-sentential switching and (2) teacher’s reasons use code switching in English classroom instruction was triggered by rhetoric reason where the teacher use English and Indonesian as the language classroom, topic of conversation based on the topic that discussed in each of meetings, and the student’s lack of vocabulary in English. Hence, it can be concluded the teachers use code switching in English classroom instruction to reach the student’s knowing and understanding about the learning in English classroom and to create the environment classroom enjoy and motivated.